2016
DOI: 10.1186/s12932-016-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Sources of salinity and arsenic in groundwater in southwest Bangladesh

Abstract: BackgroundHigh salinity and arsenic (As) concentrations in groundwater are widespread problems in the tidal deltaplain of southwest Bangladesh. To identify the sources of dissolved salts and As, groundwater samples from the regional shallow Holocene aquifer were collected from tubewells during the dry (May) and wet (October) seasons in 2012–2013. Thirteen drill cores were logged and 27 radiocarbon ages measured on wood fragments to characterize subsurface stratigraphy.ResultsDrill cuttings, exposures in pits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 39 publications
(58 reference statements)
3
47
0
Order By: Relevance
“…Interestingly, the deposition rates determined by this and other recent studies (e.g., Rogers et al, 2013;Auerbach et al, 2015;Bomer et al, in review) are similar to the local deposition rates observed across the entire Holocene (0.7-1.0 cm/year; Ayers et al, 2016). Further to the west, where sedimentation has been reduced as a result of the eastward migration of the Ganges River over the past 4000 years, the longterm deposition rates are closer to 0.1-0.2 cm/year (Flood et al, 2015).…”
Section: Spatio-temporal Variability and Future Implicationssupporting
confidence: 88%
“…Interestingly, the deposition rates determined by this and other recent studies (e.g., Rogers et al, 2013;Auerbach et al, 2015;Bomer et al, in review) are similar to the local deposition rates observed across the entire Holocene (0.7-1.0 cm/year; Ayers et al, 2016). Further to the west, where sedimentation has been reduced as a result of the eastward migration of the Ganges River over the past 4000 years, the longterm deposition rates are closer to 0.1-0.2 cm/year (Flood et al, 2015).…”
Section: Spatio-temporal Variability and Future Implicationssupporting
confidence: 88%
“…However, the initial investment and maintenance costs are even higher than for the construction of manually operated DTWs. Additionally, it should be noted that fresh groundwater recharge is limited [9,14], which means that the use of deep groundwater would probably be unsustainable. Nevertheless, the mining of deep groundwater could be a useful solution for the short term.…”
Section: Dtwsmentioning
confidence: 99%
“…In the Ganges-Brahmaputra-Meghna delta, with a population of over 170 million, unsafe drinking water is used due to drinking water resources being severely stressed. Surface water resources are polluted [5,6], meteorological water resources are subject to distinct seasonality [7,8], and shallow groundwater is often contaminated with arsenic [9][10][11][12][13]. In southwestern Bangladesh, salinity in surface water and groundwater [9,[14][15][16] puts further pressure on the available drinking water options, leading to the consumption of bacterially contaminated pond water [17] and of shallow groundwater with elevated levels of arsenic and salinity [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The northern part shows single aquifer system and aquifer complexity increases towards the south where it ends up as a multi-layer aquifer system. Several studies in Bangladesh (Ravenscroft 2003;Ahmed et al 2004;Shamsudduha and Uddin 2007;Shamsudduha et al 2011;Ayers et al 2016) and West Bengal (Acharyya et al 2000;Bhattacharya et al 1997;Goodbred et al 2003;Shamsudduha and Uddin 2007;Biswas et al 2014;Ghosal et al 2015) have stated the existence of multi-aquifer system in the Ganges Delta plain. Generalized classification schemes define two aquifer units: shallow aquifers (occurring within a depth of 150 m) and deep aquifers (occurring at depths below 150 m) in Bangladesh (Ahmed et al 2004).…”
Section: Ns Cross Sectionsmentioning
confidence: 99%